2013
DOI: 10.2217/fmb.13.102
|View full text |Cite
|
Sign up to set email alerts
|

Recent Molecular Insights into Rickettsial Pathogenesis and Immunity

Abstract: Human infections with arthropod-borne Rickettsia species remain a major global health issue, causing significant morbidity and mortality. Epidemic typhus due to Rickettsia prowazekii has an established reputation as the ‘scourge of armies’, and as a major determinant of significant ‘historical turning points’. No suitable vaccines for human use are currently available to prevent rickettsial diseases. The unique lifestyle features of rickettsiae include obligate intracellular parasitism, intracytoplasmic niche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 180 publications
(224 reference statements)
0
83
0
9
Order By: Relevance
“…typhi (Sears et al ., 2012) and R . heilongjiangensis (Qi et al ., 2013) , suggesting that surface exposed proteins may undergo methylation of Lys residues, a process that would help neutralize the highly acidic rickettsial proteins exposed to the host cytoplasm, such as Sca5 (Sahni et al ., 2013) . It is tempting to speculate that extracellular chaperones, such as PrsA, may primarily function in folding other secretory proteins, but also may themselves undergo post-translational modification to provide rickettsiae with additional surface variability and/or ligands for mediating interactions with host receptors.…”
Section: Secretory Proteins At the Host Interfacementioning
confidence: 99%
“…typhi (Sears et al ., 2012) and R . heilongjiangensis (Qi et al ., 2013) , suggesting that surface exposed proteins may undergo methylation of Lys residues, a process that would help neutralize the highly acidic rickettsial proteins exposed to the host cytoplasm, such as Sca5 (Sahni et al ., 2013) . It is tempting to speculate that extracellular chaperones, such as PrsA, may primarily function in folding other secretory proteins, but also may themselves undergo post-translational modification to provide rickettsiae with additional surface variability and/or ligands for mediating interactions with host receptors.…”
Section: Secretory Proteins At the Host Interfacementioning
confidence: 99%
“…In addition, there were more advanced lesions and more bacteria when supportive therapy was given as opposed to untreated infections. Considering that endothelial cells are recognized as key immunoreactive cells involved in host defense and inflammation (Sahni et al, 2013), some of the alterations observed in the various organs may be the result of a strong immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stimulation through the intracellular route that activates T cells and induces cytokines like IFN-␥, TNF-␣, IL-1B, and CCL5 seem to be important in eliminating pathogenic rickettsiae (Feng and Walker, 2000;Valbuena et al, 2004;Sahni et al, 2013). Infection with R. rickettsii probably occurred in guinea pigs previously infected with 'Candidatus R. amblyommii', given transient temperature increase, antibody production, and visible orchitis (one animal), but the resulting immune response efficiently eliminated R. rickettsii to levels undetectable by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…and Shigella flexneri are also known to infect macrophages (18). However, macrophages are not the primary cells targeted during Rickettsial infections (209), and Shigella spp. induce macrophage cell death instead of replicating intracellularly as a strategy of pathogenesis (210212).…”
Section: Infection Of Macrophages By Cytosolic Bacteriamentioning
confidence: 99%